Leadership in Action : In Focus - Talent Management - Engaging and Developing is Key to the Challenge - Athey, Robin (Center for Creative Leadership, 2007)
Even the best recruitment tactics will not be enough to combat today's talent challenge. High compensation packages and bonuses are easily matched by competitors. Instead, a more discerning response is required.